Effect of TiC addition on the microstructure and mechanical properties of TiN-based cermets. Issue 1 (January 2017) - Zeng, Wenmiao; Gan, Xueping; Li, Zhiyou; Zhou, Kechao
Abstract: In this paper, the influence of TiC addition on the microstructure and mechanical properties of TiN-based cermets fabricated through the powder metallurgical method was systematically investigated by scanning electron microscopy, X-ray diffraction and mechanical tests. The results showed that the TiC content had a significant effect on the microstructure evolution and mechanical properties of TiN-based cermets. When the added TiC content increased from 0 to 20 wt%, the transverse rupture strength, relative density and fracture toughness increased initially, exhibited a maximum and then decreased, while the hardness increased monotonically. As the TiC content was 10 wt%, the transverse rupture strength, relative density, fracture toughness and Rockwell hardness of TiN-based reached up to 2223 MPa, 99.87%, 15.7 MPa m 1/2 and 88.7 HRA, respectively.